Limiares da política e do tempo na filosofia de Giorgio Agamben - Barbosa, Jonnefer Francisco (2012)
The present thesis aims to address the problem of the relations between politics and time in the work of the Italian philosopher Giorgio Agamben, which is situated within four thresholds where this question is further developed: a) the problem about bare life and forms-of-life; b) the community problem; c) the state of exception; d) the relation among time, memory and history. From the inventory that Agamben will make out of the originating concepts of the treaty of Aristotle Peris Psykhês as well as the archaic Roman Law towards the definition of bare life , to the Agamben s readings on the reflections of Walter Benjamin, Hannah Arendt and Michel Foucault, which will be tackled as biopolitical hypothesis , by going through surveys on the Schmitt s exception and the reine Gewalt in Benjamin s, the thesis is intended to expose the inevitable threshold of the political problems with the discussions on time and memory within Agamben s philosophy presented below, in addition to some of the main difficulties, implications and contradictions involving its formulation. Thresholds (Schwellen) must be understood herein not only in a methodological but also epistemological sense the way that Agamben thinks its philosophy, through ontology, politics, law and esthetics and the temporary sense, the specificity of the thresholding concept to characterize the unique relation about the human time with the memory, the history and the politics